(untitled) - Kuc, Roman (United States of America, 2014)
Describes the basic components and technologies that make computer-assisted systems operate and cooperate, inviting the reader to understand by participating in the design process. This book starts with the basics and requires a working knowledge of algebra
Keywords: Electrical engineering,Kỹ thuật điện